(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
In this article, the subject of research is the development of entrepreneurial activity in the field of road transport. With the transition to a market economy in our country, as in all industries, as well as in the field of used cars, entrepreneurial activity began. The resumption of the organization of the customs union with border states, especially with the People’s Republic of China, served as the beginning of the distillation and receipt of used cars in our country. Our state borders on China and has two checkpoints: Torugart and Erkesh-tam and through which the entire flow of varieties of goods, including vehicles, passes to Kyrgyzstan. The purpose of this work is entrepreneurial activity in the field of road transport and analysis, collection of statistical data on the number of supported cars in our country, about the positive and negative consequences of this entrepreneurial activity.As well as other ways for doing business in the field of used cars, businessmen carry out through the territories of Europe, Russia and Kazakhstan, as well as from the countries of the east - Japan, which also passes through the entire eastern latitude of Russia, then Kazakhstan. Many types of vehicles pass from the indicated checkpoints every month, except for cars, various types of foreign cars, trucks from abroad to our Republic, and for used cars, customs duties are collected through customs points that enter the country’s treasury and after which their businessmen put up for sale or exchange for another product is one of the types of entrepreneurial activity in the field of transport. This type of business is mainly carried out by entrepreneurs of medium and small businesses, all this is currently carried out in the non-state sphere and is subject to state regulation. Streamlining, improving and further state regulation of this type of entrepreneurial activity will finally become a profitable sector of our economy, which will become one of the directions in the field of taxation of the country.